Analisis Kinerja Keuangan Perusahaan dengan Menggunakan Metode Rasio Keuangan: Studi Kasus pada perusahaan Tri Banyan Tirta Tbk - Jaiyanti Jaiyanti; Maria Cristina Raja; Ratih Kusumastuti (Pusat Riset dan Inovasi Nasional, 2023)
This study uses a financial ratio approach to examine the financial performance of Tri Banyan Tirta Tbk. This research is a quantitative descriptive study that uses financial data from businesses for two years between 2021 and 2022. Liquidity ratios, solvency ratios, profitability ratios, and activity ratios are all included in the financial ratio method. Based on the research results, it can be interpreted that the financial performance of Tri Banyan Tirta Tbk has decreased during the study period. Therefore, it is necessary to make efforts to improve financial performance by implementing effective and efficient business strategies and good risk management. In addition, the company also needs to improve operational performance and efficiency in the use of assets to develop the business in a sustainable manner in the future.